Postcardiotomy extracorporeal membrane oxygenation in patients older than 70 years: Characteristics, outcomes, and variables associated with mortality - Makhoul, Maged; Mariani, Silvia; van Bussel, Bas C T; Wiedemann, Dominik; Saeed, Diyar; Di Mauro, Michele; Pozzi, Matteo; Botta, Luca; Boeken, Udo; Samalavicius, Robertas; Bounader, Karl; Hou, Xiaotong; et al. (JTCVS open, 2025)
OBJECTIVES: Age is the main determinant for mortality in patients requiring postcardiotomy extracorporeal membrane oxygenation (PC-ECMO), but strategies to reverse this trend are unknown. This study investigates PC-ECMO outcomes in older patients (≥70 years) compared with younger patients (<70 years). METHODS: This retrospective study included patients who required PC-ECMO between 2000 and 2020. Variables independently associated with in-hospital mortality were identified using mixed Cox proportional hazards models. RESULTS: The study included 2057 patients (mean age: 62.3 [first and third quartile: 19-94]; male patients: n = 1213 [59%]): 1376 (67%) were <70 years and 680 (33%) were ≥70 years old. Older patients had more preoperative comorbidities, whereas younger patients had lower cardiac function and more preoperative intubation and vasopressor use. In-hospital mortality was 56.3% (n = 775) and 68.8% (n = 468) in the <70 year and ≥70 year groups, respectively (P < .001). The 7-year postdischarge survival rate was greater for the younger patient group (P < .001). Variables associated with in-hospital mortality in older patients were previous stroke (hazard ratio [HR], 1.39; 95% confidence interval [CI], 1.05-1.84), preoperative right ventricular failure (HR, 1.45; 95% CI, 1-2.1), aortic surgery (HR 1.65; 95% CI, 1.2-2.2), and postoperative complications including bleeding (HR 1.24; 95% CI, 1.0-1.5), cardiac arrest (HR, 1.65; 95% CI, 1.3-2.1), and right ventricular failure (HR, 1.29; 95% CI, 1.0-1.6). CONCLUSIONS: PC-ECMO mortality is high in older patients. Preoperative factors including previous stroke and right ventricular failure and postoperative factors including bleeding, cardiac arrest, and right ventricular failure should be targeted to reduce in-hospital mortality after appropriate initial selection in older patients.
Keywords: age; extracorporeal membrane oxygenation; cardiac surgery; mortality; postcardiotomy cardiogenic shock; mechanical circulatory support